Enhancing Performance in Cape Town’s SMME Sector by Outsourcing Accounting Strategy - Tshibangu-Mutonji, Tania; Obokoh, Lawrence Ogechukwu; Johnson, Ian Lyndon (Economics and Entrepreneurship: The Proceedings of the 10\(^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
This study investigated the impact of outsourcing accounting strategies on the performance of small, medium, and micro enterprises (SMMEs) in the retail and service sectors in Cape Town, South Africa. A quantitative research design was employed, with data collected through an online survey and door-to-door distribution to a sample of 102 respondents. The analysis was conducted using XLSTAT software, applying partial least square structural equation modelling (PLS-SEM) for structural analysis. Cronbach’s Alpha measured reliability, while the Average Variance Extracted (AVE) assessed model validity. The findings indicate that outsourcing accounting functions positively influenced SMME performance, particularly in reducing operational costs and enhancing time management. These findings suggest that outsourcing provides a viable solution for SMMEs seeking operational efficiency and sustainability in a resource-constrained environment. Additionally, the findings reveal the strategic value of outsourcing for SMMEs within South Africa’s dynamic economic landscape. The study recommends outsourcing as a strategy for SMMEs to improve cost and time management.